Inventory Information System on Welding Techniques Workshop - Fadli Muhlisin; Safaruddin H. Al Ikhsan; Fitrah S. Fajar Kusuma (Indonesian Journal of Social Research (IJSR), 2019)
In managing laboratory equipment at SMK Negeri 1 Gunungputri, they still use manual methods and the toolman or head of the workshop does not collect data continuously, causing data and goods in the field to be incompatible, then there is no inventory number that causes lost items cannot be identified, therefore needed an Information System Inventory of Welding Engineering Workshop. This system uses the System Development Life Cycle method with Object Oriented Design modeling, with an Information System Inventory Workshop Welding Techniques can make it easier to identify every item in the field, reduce errors in terms of storage of goods, search for data and can facilitate the search for goods, especially in the Engineering workshop Welding.